Q. 1 E4.7( 11 Votes )

<span lang="EN-US

Answer :

If LHS is


4p + 3p + 2p + p – 9p


Then RHS would be


4p + 3p + 2p + p – 9p


= p(4 + 3 + 2 + 1–9)


= p(10–9)


= p


The error is p instead of 0


Hence 4p + 3p + 2p + p–9p = p


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Questions on FactorizationQuiz | Questions on FactorizationQuiz | Questions on Factorization41 mins
Quiz | Important Questions on FactorisationQuiz | Important Questions on FactorisationQuiz | Important Questions on Factorisation35 mins
NCERT | Factorisation ProblemsNCERT | Factorisation ProblemsNCERT | Factorisation Problems38 mins
Algebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak AreasAlgebraic Identities - Mark your Weak Areas41 mins
Champ Quiz | Division of PolynomialsChamp Quiz | Division of PolynomialsChamp Quiz | Division of Polynomials33 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics

<span lang="EN-USAP - Mathematics